Pelvic inflammatory disease: Medical and surgical treatment - Celis López, Alfredo (2015)
A crucial point in the management of pelvic inflammatory disease (PID) is to determine the most appropriate treatment for each case. Usually the initial management is outpatient. But depending of the severity hospitalization might be required. Taking into account the polimicrobial nature of this entity, antibiotic therapy will be broad spectrum and the election will be directed to the most frequent microbes. Treatment should not only be directed to the acute process eradication but to the prevention of its complications, such as chronic pelvic pain, infertility and ectopic pregnancy, which can be avoided or minimized if a precocious, aggressive and broad coverage is done. The most severe forms of pelvic inflammatory disease presentation are tubo-ovarian abscess and pelvic abscess. Treatment of these pathologies has varied on time from a very radical conduct in the pre-antibiotic era to a more conservative conduct with preservation of reproductive organs. This review has the objective to present the different current regimes of antibiotic treatments for PID management as well as surgical treatment alternatives for pelvic abscess.